Penerapan Model Pembelajaran Discovery Learning Berbantuan Zep Quiz untuk Meningkatkan Hasil Belajar Siswa Kelas X pada Materi Microsoft Word di MAN 1 Kuningan - Novitasari, Tia; Nasrulloh, Sofhian Fazrin (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the improvement of student learning outcomes through the application of the Discovery Learning learning model assisted by Zep Quiz on Microsoft Word material in class X MAN 1 Kuningan. This study uses a quantitative approach with a Pre-Experiment One Group Pretest-Posttest design. The study population was 178 students, while the research sample was 29 students of class X A selected using a purposive sampling technique. The research instruments were pretest and posttest to measure learning outcomes and student response questionnaires to the implementation of learning. Data analysis was carried out through normality tests and paired sample t-tests. The results showed an increase in student learning outcomes after the application of the Discovery Learning model assisted by Zep Quiz, indicated by an increase in the average score from 60.34 in the pretest to 81.38 in the posttest with a difference of 21.04. The results of the paired sample t-test showed a significance value of 0.000 (p <0.05), which means there was a significant difference in learning outcomes before and after the application of the learning model. Student responses to the use of Zep Quiz were also in the very positive category. Thus, the Discovery Learning model assisted by Zep Quiz is effective in improving student learning outcomes and engagement in Microsoft Word material.